Underwater to above water LoRaWAN networking: Theoretical analysis and field tests. (15th June 2022) - Cappelli, Irene; Fort, Ada; Mugnaini, Marco; Parrino, Stefano; Pozzebon, Alessandro
Abstract: The aim of this paper is to demonstrate the exploitability of Long Range Wide Area Network (LoRaWAN) networking to set up a wireless transmission channel allowing the real time data collection from underwater depths up to more than 1 m. To this aim, a theoretical analysis is carried out to determine the actual feasibility of this link taking into account the technical features of the LoRa channel. Following this analysis, field tests in a swimming pool have been performed analyzing the transmission performance in terms of Received Signal Strength Indicator (RSSI) and Signal to Noise Ratio (SNR) for different transmission parameters and at increasing depths. Moreover, two test campaigns varying the antenna's sensor node and the packet payload length have been performed. Experimental results have seen a good corroboration of the theoretical analysis with efficient underwater LoRaWAN data transmission at depths up to 110  ± 5  cm, considering 14 dBm transmitted power. Highlights: Underwater to Above Water LoRaWAN connectivity is tested. Field tests are performed in a swimming pool. Different configurations are tested at growing depths. Transmission is tested also for different payload lengths and with different antennas. Data transmission is successfully performed at depth up to 110 cm.